Aplicação de rejeito de mineração de ouro na produção de tijolo de solo-cimento - Ana Cláudia Franca Gomes (2021)
Our current production system works in a linear way, allowing the overexploitation of natural resources and large accumulation of waste. One way to reduce pressure on such resources is to apply the concept of circular economy in mining, which encourages the use of tailings as input for the production of new products. The aim of this work was to evaluate the use of gold mining tailings in the production of soil-cement bricks formed by cement, tailings and soil (collected in Peixoto de Azevedo – Mato Grosso, Brazil, in the Bioclimatic Zone 8). Soil-cement bricks are earth building materials that are gaining prominence for their environmental advantages. In Brazil, the technical standard NBR 8491 covers values for the compressive strength (ft) and water absorption (A) of these bricks. However, the environmental and thermal characterizations of this material constitute important assessments, since they are related to the hazard and the thermal comfort of these masonry components. It was observed that the higher the soil fraction, the greater the compressive strength (ft) and the lower the water absorption (A) of the brick. The mixture with the addition of 50% of soil reached values of ft = 3.1MPa and A = 17.0%. However, even if it meets the specifications of NBR 8491, each mining tailing has unique characteristics of hazardousness. Therefore, the brick with 50% of soil was evaluated according to NBR 10004 in which it was classified as non-dangerous, but not inert due to the high content of aluminum. The chemical evaluation showed phases of cement hydration that are related to the stabilization of contaminants such as cyanide. On the results obtained in the thermal characterization, a specimen was built with the bricks with the addition of 50% of soil in wich the absorptance (α) was evaluated using the ALTA II spectrometer, and its thermal transmittance (U) and thermal resistance (RT) through the hot box method (ISO 9869). The results enabled the calculation of the thermal capacity (CT), thermal lag (φ) and solar factor (FSO) of the specimen, which were compared to the Brazilian Technical Standards NBR 15575-4 and NBR 15220 for Bioclimatic Zone 8. As a result, the specimen showed values of absorptance α = 0.71, termal transmittance U = 2.47Wm-²K-1, termal capacity CT = 273.43 kJm-²K-1, termal lag φ = 6.02 h and solar fator Fso = 6.81%, meeting the requirements of the first standard, but failing the second. It is suggested, then, that the bricks be painted lighter tones (to decrease the value of α), or that a layer of lining mortar be incorporated in the external or internal face of the specimen in order to increase its thermal lag (φ). Finally, the tailing studied demonstrated their potential use as a raw material in the manufacture of soil-cement bricks by meeting the Brazilian’s specification NBR 8491. It is suggested that new bricks with higher proportions of soil or cement be evaluated.